PENGARUH PERSEPSI UMKM DAN PENGGUNAAN INFORMASI AKUNTANSI TERHADAP TINGKAT KEBERHASILAN UMKM KOTA PALEMBANG: SURVEI UMKM DI KOTA PALEMBANG - Bakti, Melinia; Putri, Andini Utari; Meiriasari, Vhika (LPPM Universitas Bina Bangsa, 2025)
This research aims to examine the influence of MSME perceptions and use of accounting information on the success rate of MSME. A total of 100 respondents were cellected by distributing questionnaires to MSMEs in the city of Palembang using the Purposive Sampling technique and the Slovin formula. The analysis used in this research is a quantitative method. The resukts if the abalysis show that partially the perception of MSMEs has a negative and significant effecton the seuccess of MSMEs in the city of Palembang with a significant value smaller than the predetermined value (0,000 < 0,05) while the use of accounting information has a significant effect on the success of MSMEs in the City of Palembang with a significant effect on the success of MSMEs in the city of Palembang (0,000 < 0,05).